Comparison of the Opinions of Adolescents With Different Orthodontic Treatment Needs - Larisa Krekmanova; Shams Shakrchi; Amina Gicic; Julia Naoumova (Wiley, 2024)
ABSTRACT Background The aim of this study was to compare oral health‐related quality of life (OHRQoL) among adolescents granted (G) versus not granted (NG) publicly funded orthodontic treatment. Materials and Methods Adolescents aged 15-20 years who were granted versus not granted publicly funded orthodontic treatment responded to a web‐based survey, assessing OHRQoL in relation to functional impact, psychological impact, and motivators for orthodontic treatment. Before the survey, pretesting of the questionnaire was conducted to ensure its reliability. Differences between the groups were tested using the chi‐squared and Mann-Whitney U‐tests. Reliability was assessed using Cohen's κ and Pearson's correlation coefficient during the pretest phase. Results One hundred and forty patients, equally distributed between a G and an NG group, responded to the survey. Gender, age, and demographic distribution were comparable in both groups. All respondents expressed a high subjective treatment need and similar answers regarding functional aspects. Orthodontic treatment motivators (G: 86.2% and NG: 94.7%, p = 0.443) were primarily related to improved self‐esteem, overall well‐being, facial appearance, and being able to laugh without embarrassment. The NG group expressed a more negative OHRQoL impact due to the appearance of their teeth compared with the G group (p < 0.001) and a negative impact caused by the position of their teeth (p < 0.001). Conclusions Orthodontic treatment need indices should aim to reinforce subjective measures as adolescents express similar motivators for orthodontic treatment, regardless of the clinician's objectively based decision about treatment need.